Analysis of Food Vlogger Content Creativity on Consumer Buying Interest with Viral Marketing as a Mediation Variable (Survey on Sukabumi Culinary Followers on Instagram) - Sintia Fitra Aziza; Kokom Komariah; Resa Nurmala (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Information and communication technology has deeply ingrained in people's lives. It's as if people now live